Australian Track & Field Coaches Association
Founded in 1974, the ATFCA grew and was successful in outlining plans and activities to educate coaches to promote the sport of track and field. Funded initially by the Rothmans National Sport Foundation, this lasted for twenty years, until the Foundation closed its doors.